Placental mTOR Signaling and Sexual Dimorphism in Metabolic Health across the Lifespan of Offspring - Megan Beetch (MDPI AG, 2021)
Robust evidence of fetal programming of adult disease has surfaced in the last several decades. Human and preclinical investigations of intrauterine insults report perturbations in placental nutrient sensing by the mechanistic target of rapamycin (mTOR). This review focuses on pregnancy complications associated with placental mTOR regulation, such as fetal growth restriction (FGR), fetal overgrowth, gestational diabetes mellitus (GDM), polycystic ovarian syndrome (PCOS), maternal nutrient restriction (MNR), preeclampsia (PE), maternal smoking, and related effects on offspring birthweight. The link between mTOR-associated birthweight outcomes and offspring metabolic health trajectory with a focus on sexual dimorphism are discussed. Both human physiology and animal models are summarized to facilitate in depth understanding. GDM, PCOS and fetal overgrowth are associated with increased placental mTOR, whereas FGR, MNR and maternal smoking are linked to decreased placental mTOR activity. Generally, birth weight is reduced in complications with decreased mTOR (i.e., FGR, MNR, maternal smoking) and higher with increased mTOR (GDM, PCOS). Offspring display obesity or a higher body mass index in childhood and adulthood, impaired glucose and insulin tolerance in adulthood, and deficiencies in pancreatic beta-cell mass and function compared to offspring from uncomplicated pregnancies. Defining causal players in the fetal programming of offspring metabolic health across the lifespan will aid in stopping the vicious cycle of obesity and type II diabetes.